TERTIARY LANGUAGE PLANNING AND CAREER DEVELOPMENT: CHALLENGES TO VIETNAMESE STUDENTS - Thom Thom, Nguyen Thi; Ngoc Thuy, Bui Thi; An, Nguyen Duc (VNU Journal of Foreign Studies; Vol 36 No 4, 2020)
Research in the field of English language education has shifted towards interrogating the real role of English in development across disciplines and countries. Vietnam English language policy, especially the National Foreign Languages Project (The NFL Project), have promoted English as a key success factor for Vietnamese students in the labour market as well as the well-being of the nation. This paper focuses on examining the notion of development which investigates the roles of English in Vietnamese tertiary students’ employability. The researchers conducted 527 surveys with tertiary students in four university in the North Vietnam. Moreover, five students and three EFL tertiary instructors from each institution were selected to participate in a follow-up semi-structured interview (N = 32). The results indicated students’ limited level of confidence in both their English skills as well as career-related skills performed in English. In other words, students showed their lack of sufficient English for employability purposes. Aligning the research results with the promising and well-intended agendas of ELP and The NFL Project illuminates a clear mismatch between English and employability. In reality, the relationship between English language education and career development is highly complex and contested, which may influence students’ full development in the long run. Towards the end, the paper offers suggestions for improving pedagogies, policies and practices to promote English as one of vital employability skills for multifaceted personal and national developments.